Asciminib, a novel allosteric inhibitor of BCR‐ABL1, shows synergistic effects when used in combination with imatinib with or without drug resistance - Naoki Okamoto; Kenta Yagi; Sayaka Imawaka; Mayu Takaoka; Fuka Aizawa; Takahiro Niimura; Mitsuhiro Goda; Koji Miyata; Kei Kawada; Yuki Izawa‐Ishizawa; Satoshi Sakaguchi; Keisuke Ishizawa (Wiley, 2024)
Abstract In the treatment of chronic myeloid leukemia (CML), resistance to BCR‐ABL inhibitors makes it difficult to continue treatment and is directly related to life expectancy. Therefore, asciminib was introduced to the market as a useful drug for overcoming drug resistance. While combining molecular targeted drugs is useful to avoid drug resistance, the new BCR‐ABL inhibitor asciminib and conventional BCR‐ABL inhibitors should be used as monotherapy in principle. Therefore, we investigated the synergistic effect and mechanism of the combination of asciminib and imatinib. We generated imatinib‐resistant cells using the human CML cell line K562, examined the effects of imatinib and asciminib exposure on cell survival using the WST‐8 assay, and comprehensively analyzed genetic variation related to drug resistance using RNA‐seq and real‐time PCR. A synergistic effect was observed when imatinib and asciminib were combined with or without imatinib resistance. Three genes, GRRP1, ESPN, and NOXA1, were extracted as the sites of action of asciminib. Asciminib in combination with BCR‐ABL inhibitors may improve the therapeutic efficacy of conventional BCR‐ABL inhibitors and prevent the development of resistance. Its dosage may be effective even at minimal doses that do not cause side effects. Further verification of this mechanism of action is needed. Additionally, cross‐resistance between BCR‐ABL inhibitors and asciminib may occur, which needs to be clarified through further validation as soon as possible.